2023
DOI: 10.7759/cureus.46609
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Immune-Inflammation Index as a Biomarker for Rheumatoid Arthritis Progression and Diagnosis

Duygu Tutan,
Ayşe G Doğan

Abstract: Introduction Rheumatoid arthritis (RA) is a chronic autoimmune condition that causes systemic inflammation and affects multiple joints. It is characterized by joint warmth, swelling, pain, and the formation of invasive synovial tissue known as pannus, which contributes to cartilage and bone degradation. Pan-immune-inflammation value (PIV), a marker derived from complete blood count parameters, has shown promise in predicting prognosis in various cancer types and pediatric conditions associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The survival rate was lower in those who had higher PIV values at the time of diagnosis [ 19 ]. Additionally, Tutan et al reported significantly elevated PIV in patients with active rheumatoid arthritis compared to those in remission [ 34 ]. As far as we know, previous studies have not investigated the relationship between PIV and amyloidosis and disease severity in FMF patients.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate was lower in those who had higher PIV values at the time of diagnosis [ 19 ]. Additionally, Tutan et al reported significantly elevated PIV in patients with active rheumatoid arthritis compared to those in remission [ 34 ]. As far as we know, previous studies have not investigated the relationship between PIV and amyloidosis and disease severity in FMF patients.…”
Section: Discussionmentioning
confidence: 99%